The Modification of Rotation - Advancement Flap Made in 1950 - Predrag Knežević; Marko Vuletić; Igor Blivajs; Emil Dediol; Darko Macan; Mišo Virag (University of Zagreb. School of Dental Medicine, 2017)
The early techniques of cleft lip repair involved the straight-line technique, the triangular flap technique or some kind of geometric line (triangular, quadrangular closure). A turning point in cleft lip surgery was in 1955 when doctor. Millard presented his method: the rotation-advancement technique or flap, at the First International Congress of Plastic Surgery in Stockholm. Today, the technique, with or without some modifications, is used by more than 85% of cleft surgeons around the world. We are presenting a patient with complete unilateral cleft lip and palate who underwent surgery sixty-five years ago. The scar on his lip was similar to rotation advancement line. Cheiloplasty was performed by Professor Šercer in 1950, five years before Millard's publication. Professor Ante Šercer was an internationally recognized Croatian scholar in the area of ear, nose and throat diseases. He also gave a significant contribution to surgical management of velopharyngeal insufficiency and plastic surgery of the nose and ear.